Adsorption potential of hydrochar derived from hydrothermal carbonization of waste biomass towards the removal of methylene blue dye from wastewater - Saini R.; Pandey M.; Mishra R.K.; Kumar P. (My University, 2025)
Industrialization plays a major role in water pollution through the discharge of effluents produced by various industries such as textiles, paper, leather, cosmetics, and paint manufacturing. Methylene blue (MB), a positively charged synthetic dye extensively utilized in these sectors, poses significant toxicity and chemical stability concerns. Adsorption has emerged as a highly efficient and cost-effective approach for wastewater treatment, offering enhanced removal efficiency, rapid response, and operational simplicity. This study explores the enhanced adsorption potential of hydrochar, which exhibits a higher capacity and faster action compared to biomass. Utilizing the hydrothermal carbonization (HTC) process, hydrochar was produced from sunflower stalks (biomass) to assess its effectiveness in removing MB dye from synthetic wastewater. The physical and chemical characteristics of hydrochar and biomass were examined. Through batch adsorption experiments, various parameters, including time, adsorbent dose, pH, initial MB dye concentration, and temperature, were systematically investigated. Results revealed that due to its greater surface area, surface complexation, and pore volume, hydrochar exhibited a superior adsorption capacity of 49.37 mg/g compared to biomass, which achieved 24.24 mg/g under optimal conditions. Additionally, various isotherm, kinetic, and mass transfer models were analyzed to understand the adsorption behavior of MB on both adsorbents. Experimental results for both adsorbents conformed well with the Sips isotherm and pseudo-second-order kinetic model. Notably, the Sips model yielded ks values of 0.433 and 0.636 (L/mg)1/m for biomass (BM) and hydrochar (HC), respectively, while the kinetics’ k values were determined as 0.0069 and 0.0036 (g/mg·min). Further analysis through mass transfer studies indicated that the rate-limiting step encompassed both intra-particle diffusion and film diffusion processes. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.